Efficacy and safety of traditional Chinese medicine for the treatment of pancreatic cancer: An overview of systematic reviews and meta-analyses - Wang, Jing; Wang, Qiuyuan; Zhang, Peitong; Zhang, Ruoqi; He, Jie (Frontiers in Pharmacology, 2022)
Pancreatic cancer is a highly malignant tumor with poor prognosis. Currently available Western medical management strategies are unable to prolong the survival time and reduce mortality of patients with pancreatic cancer. Traditional Chinese medicine has achieved promising results in many clinical studies. This systematic review and meta-analysis (SR/MA) aimed to explore the benefits and evaluate the quality of evidence of traditional Chinese medicine-based interventions for preventing and treating pancreatic cancer. A systematic search of eight databases for SRs/MAs of randomized controlled trials on traditional Chinese medicine treatment for pancreatic cancer was conducted (from inception to April 2022). The methodological quality of the SRs/MAs was assessed using AMSTAR 2.0, and the quality of evidence was evaluated using the GRADE guide. nine SRs/MAs, including 145 randomized controlled trials, were considered eligible for this study. The literature were published between 2014 and 2022. The sample size of randomized controlled trials in the MAs ranged from 336 to 1,989. The methodological quality of the nine studies was critically low. Among the 59 outcome indicators of the 9 SRs/MAs, 7, 33, and 19 had moderate-, low-, and critically low-quality evidence, respectively, while high-quality evidence was not identified. The results for the long-term indicators, short-term indicators, and adverse reactions in the SRs/MAs displayed consistencies as well as differences. In conclusion, the methodological and evidence quality of current evidence is generally low, highlighting the need for additional focus on implementation processes. Some evidence with moderate quality validated that several specific TCM was optimum in improving the short-term clinical efficacy. However, more objective and high-quality investigations are warranted to verify the efficacy of traditional Chinese medicine for pancreatic cancer.